Pengaruh Leverage, Profitability, Sales Growth, Age, Size dan Institutional Ownership terhadap Tax Avoidance - Sumadi, Rizki Ramadhan; Susanto, Yulius Kurnia (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
Tax Avoidance is defined as a legal activity (efforts made by taxpayers to minimize the tax burden).The objective of this research is to obtain empirical evidence regarding the influence of Leverage, Profitability, Sales Growth, Size, Age and Institutional Ownership (variable X) on Tax Avoidance (variabel Y) with the object of research on manufakturing companies listed on the indonesian Stock Exchange (IDX) from 2019 – 2021 years.The population in this study was obtained using sampling technique with purposive sampling method where this study amounted to 195 company data. The results of this study explain that Sales Growth, Age, Size, and Institutional Ownership have no effect on Tax Avoidance. While Leverage positif effect and Profitability Negative effect on Tax Avoidance.